Hospitals as Service Products: Service Quality and Patient Satisfaction - Chyntia Putriasni Kurnia; Cindy Charoline; Agustina Br Ginting; Beradona Beradona; Abdurrahman Samarqandy Rasta; A Rohendi (Research of Service Administration Health and Sains Healthys, 2026)
Hospitals are healthcare institutions that function as service providers with unique characteristics distinct from tangible products, making service marketing perspectives essential for improving service quality and patient satisfaction in a competitive healthcare environment. This study employed a Systematic Literature Review (SLR) using the PRISMA protocol to identify and synthesize empirical and conceptual evidence related to hospital service characteristics, service quality dimensions, service marketing mix, and factors influencing patient satisfaction and loyalty. Literature searches were conducted in Scopus, PubMed, Google Scholar, EBSCO, and ProQuest for publications from 2013–2024. From 847 identified articles, 42 met the inclusion criteria and were analyzed. The findings revealed five dominant themes: IHIP characteristics in hospital services, SERVQUAL-based service quality dimensions, implementation of the 8P service marketing mix, the relationship between service quality and patient satisfaction and loyalty, and the role of human resources in achieving service excellence. The review confirms the relevance of the service marketing framework proposed by Christopher Lovelock and Lauren Wright in understanding hospitals as service products. Overall, hospitals require a holistic and patient-oriented management approach, where integrating service marketing concepts such as the flower of service, 8P marketing mix, and service quality management can significantly enhance patient satisfaction and loyalty.